A New Strategy to Regulate the Selectivity of Photo-Mediated Catalytic Reaction - Qian, Kun (Frontiers in Chemistry, 2021)
Here we developed a new method for regulating the selectivity of photo-mediated catalytic reaction by manipulating the surface charge of Au/TiO2 (Gold/Titanium Dioxide) catalysts within chemical reaction timescales. Two kinds of photo-catalytic reactions, hydrogenation of acetophenone and benzyl alcohol oxidation, have been applied to investigate the photo-catalytic performance over Au/TiO2 catalysts with tunable surface charges. We found that a suitable timescale of switching surface charge on Au would benefit for the enhanced quantum efficiency and play different roles to the selectivity of desired products in hydrogenation and oxidation reactions. Au/TiO2 catalyst under 5 μs flashing light irradiation exhibits much higher selectivity of 1-phenylethanol in the hydrogenation of acetophenone than that under continuous light and 5s flashing light irradiation, by contrast, Au/TiO2 catalysts under both flashing light and continuous light irradiation exhibit a similar selectivity of benzaldehyde in benzyl alcohol oxidation. Our findings will benefit for a better understanding of electronic structure mediated reaction mechanism and be helpful for achieving highly efficient photocatalytic systems.